2022
DOI: 10.3389/fphar.2021.798938
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mechanisms of Action and Efficacy of Vitamin E Components in Antioxidant Cytoprotection of Human Retinal Pigment Epithelium

Abstract: The purpose of this study was to determine if different vitamin E components exhibit similar efficacy and mechanism of action in protecting Retinal pigment epithelium (RPE) cells from oxidative damage. We hypothesized that α-tocopherol (αT) is unique among vitamin E components in its cytoprotective mechanism of action against oxidative stress in RPE cells and that it requires protein synthesis for optimal antioxidant effect. We used cell viability assays, fluorescent chemical labeling of DNA and actin and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…We previously reported that αT, but not tBHP, exposure of hTERT-RPE cells induced the expression of Nrf2 but did not lead to the nuclear translocation of Nrf2 ( 10 ). Exposure to tBHP, on the other hand, had no effect on Nrf2 expression but it led to an increase in Nrf2 nuclear translocation, suggesting it had become activated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that αT, but not tBHP, exposure of hTERT-RPE cells induced the expression of Nrf2 but did not lead to the nuclear translocation of Nrf2 ( 10 ). Exposure to tBHP, on the other hand, had no effect on Nrf2 expression but it led to an increase in Nrf2 nuclear translocation, suggesting it had become activated.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were exposed to tocopherols for 24 hours prior to treatment with the 100μM tert-butyl hydroperoxide (tBHP), the oxidant, or water as a vehicle control for 24 hours. The six paired treatment groups (24h treatment 1 - 24h treatment 2) were vehicle-control, vehicle-tBHP, αT-control, γT-control, αT-tBHP and γT-tBHP, the same as in a previous study ( 10 ) (see Supplemental Figure 1 ). A tocopherol concentration of 100μM was selected based on previous reports (~25 – 32 μM vitamin E in serum) and calculations based on the daily recommendation dose of vitamin E at 400IU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common experimental model to study AMD and oxidative stress is the use of the ARPE-19 cell line, immortalized human RPE cells, and human telomerase reverse transcriptase (hTERT)-RPE. In Duncan et al, 2022 they demonstrate that α-tocopherol, γ-tocopherol, δ-tocopherol, and α-tocotrienol all exhibited similar, but not identical, antioxidant activity. In addition, exposure time is important for its protective properties against oxidative stress.…”
Section: Molecular Mechanisms Of Vitamin E Signaling In the Retinamentioning
confidence: 91%
“…In addition, exposure time is important for its protective properties against oxidative stress. Synthesis of new proteins was also found to be partially required with α-tocopherol, but not γ-tocopherol, within a 24-h period and before exposure to tertiary butyl hydroperoxide (tBHP) for optimal cytoprotection ( Duncan et al, 2022 ). In another study, ARPE-19 cells were subjected to pre-treatment of ≥2.5 mM α-tocopherol, which significantly decreased oxidative stress-induced activator protein-1 (AP1) transcription factor expression at 14 h but was not further reduced with higher levels of α-tocopherol ( Yin et al, 2011 ).…”
Section: Molecular Mechanisms Of Vitamin E Signaling In the Retinamentioning
confidence: 99%